Compliance with national guidelines for antibiotic prophylaxis in hip fracture patients: a quality assessment study of 13 329 patients in the Norwegian Hip Fracture Register - Wender Figved; Lars Nordsletten; Tom Lian; Eva Dybvik; Jan-Erik Gjertsen; Håvard Dale; Marianne Westberg (BMJ Open, 2020)
Objective We assessed compliance with new guidelines for prophylactic antibiotics in hip fracture surgery in Norway introduced in 2013.Design The data from the Norwegian Hip Fracture Register was used to assess the proportion of antibiotics given according to the national guidelines.Setting All hospitals in Norway performing hip fracture surgery in the period from 2011 to 2016.Participants We studied 13 329 hemiarthroplasties (HAs) for acute hip fracture.Main outcome measure Type and timing between first and last dose of prophylactic antibiotics compared with the national guidelines.Results Before the guidelines were introduced, the recommended drugs cephalotin or clindamycin was used in only 86.2% of all HAs. In 2016, one of the two recommended drugs was administered in 99.2% of HAs. However, hospitals’ adaption of the recommended administration of the two drugs improved slowly, and by the end of the study period, only three out of five HAs were performed with the correct drug administered in the correct manner. We found major differences in compliance between hospitals.Conclusions The change towards correct administration of antibiotic prophylaxis was varied both when investigating university and non-university hospitals. We suggest that both hospital leaders and the national Directorate of Health need to investigate routines for better dissemination of information and education to involved parties. Strong leadership concerning evidence-based guidelines on antibiotic prophylaxis in surgery may take away some autonomy from executing healthcare professionals, but will result in better patient care and antibiotic stewardship.